Measuring Quality of Life (QOL) of Parents of Children with Disabilities in the State of Kuwait: An Exploratory Study of Parents’ Perceptions - Al Refaie , Tagreed; Al Mowaizri, Naser (Jordan Journal of Educational Sciences, 2016)
A great recognition is recently devoted to the importance of measuring (QOL) of children with disabilities Quality of Life (QOL). This recognition is considered essential in the Arab world. The purpose of the current study was to measure the concept of QOL of parents of children with disabilities in the State of Kuwait. A convenient sample of 140 parents participated in the study. Their perceptions of QOL were measured using the Arabic translated version of World Health Organization Quality of Life Brief (WHOQOL-BREF). Results of the study revealed that parents’ perceptions or evaluations of their QOL levels for each of the four domains and the total score of the WHOQOL-BREF were in the range of medium to high levels. Results of independent sample t. test and One-way ANOVA revealed no statistically significant differences were found and attributed to any variable related to parents’ variables or children’s variables. Although, parents of children with Autism and parents of children with Intellectual Disabilities had the lower mean scores of QOL in comparison with parents’ of children with Sensory and Physical and Health impairments; however, these differences in means were not significant. Results of the study warrant for future investigations by other research studies. Further explanations and recommendations are presented in the study